Policy Implementation of 9 Years of Compulsory Learning Program and Eradication of Illute Illusion In Nabire District - Rahman Hakim, Arief (Universitas Negeri Makassar, 2021)
Education has an important role in the process of improving the quality of human resources. Improving the quality of education is an integrated process in the process of improving the quality of human resources. The role of education is very much needed and demands attention and participation from all parties. In Article 31 of the 1945 Constitution, education is a right for every citizen, the Government is well aware of the need to improve the quality of education as a tool to improve the quality of human resources. Through Law No. 20 of 2003 concerning the national education system and Presidential Instruction No. 5 of 2006 2006 concerning the National Movement for the Acceleration of Completion of Compulsory Education for Nine Years of Basic Education and Eradication of Illiteracy. Therefore, there are still many children who drop out of school, especially in Nabire Regency. Most children drop out of school because of a lack of awareness of the importance of education and the role of parents in encouraging their children. In addition, the school environment that affects student learning includes classroom infrastructure, inadequate and inadequate building conditions. In this study using qualitative research methods, namely a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. Qualitative research, data collection is carried out in natural conditions, primary data sources, and data collection techniques are mostly on instrumental observation, as well as in-depth interviews. This study concludes that the implementation of the 9-year compulsory education program policy in Nabire sub-district has not been implemented effectively due to inconsistency. Then policy implementers have not given a positive attitude which is marked by weak coordination in policy implementation.